The PENGARUH POLA PENGASUH ORANG TUA TERHADAP KREATIVITAS ANAK USIA DINI DI TK AISYIYAH KlODRAN COLOMADU KARANGANYAR - Alfina Endah Sulis Setiawati; Wili Astuti (Universitas Pendidikan Ganesha, 2023)
Creativity is one of the 21st-century skills that young children must possess; creativity can be demonstrated through the child's ability to express the thoughts and ideas in their minds and positively impact their future. The level of creativity in children can be influenced by several factors, one of which is parents' parenting style. This research aims to analyze the influence of parenting styles on early childhood creativity. This research is classified as a quantitative type of research, with a population of 56. The research was conducted using probabilistic techniques with proportional stratified random sampling. The final sample size in this study was 36 children. Data collection in this research was carried out using observation, documentation, and questionnaire distribution methods, with the research instrument as a closed questionnaire with a Likert scale. The data obtained in the research was then analyzed using the t-test analysis technique. The results of the data analysis show that authoritarian parenting harms children's creativity. In other words, the higher the parenting style, the less creative the child is.On the other hand, democratic parenting has a positive effect. It means the higher the parenting style, the more creative the child will be. So, there is an influence of parental parenting on children's creativity.